STRATEGI GURU DALAM PENERAPAN PEMBELAJARAN DEEP LEARNING PADA KELAS 5 DI MI AN-NAFIRA PALEMBANG - Faisal; Yunita; Ihsan Nur Fadli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the strategies used by fifth-grade teachers in implementing Deep Learning in classroom at MI An-Nafira Palembang. This research employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews, participatory observation, and documentation studies involving fifth-grade teachers as the main informants and the principal as a supporting informant. Data analysis used the interactive model by Miles, Huberman, & Saldaña (2014), with source triangulation and technique triangulation to ensure data validity. The findings reveal that teachers have implemented Deep Learning strategies across three main aspects: (1) in the planning aspect, teachers designed lessons using essential questions and integrated inquiry and collaborative activities into lesson plans; (2) in the implementation aspect, teachers applied higher-order questioning techniques, collaborative group discussions, and simple project-based learning connected to students' real-life contexts; and (3) in the evaluation aspect, teachers used ongoing formative assessment and direct feedback to monitor students' developing understanding. However, the implementation still faces challenges including limited planning time, insufficient learning resources, and the need to strengthen teachers' understanding of the Deep Learning framework. These findings are expected to serve as a reference for teachers and education stakeholders in improving the quality of learning in madrasah ibtidaiyah.